Aspectos fenomenológicos y políticos-criminales del sexting: aproximación a su tratamiento a la luz del Código Penal chileno = Phenomenological and criminal policy aspects of sexting : an approach to its treatment under the Chilean Criminal Code - Scheechler Corona, Christian (Política criminal, 2019)
Convergence between sexual delinquency and the information and communication technologies has allowed the emergence of a series of criminally relevant phenomena, such as sexting or cybergrooming. These phenomena become particularly important given the involvement of minors -sometimes even with the exclusion of adults -which raises the issue of trying to subsume these phenomena into criminal offences under the Chilean law, which protects their sexual freedom, indemnity, or privacy. In this paper, I will focus on the analysis of the first of said phenomena. I will try to identify the characteristic elements of sexting, in order to delimit it and differentiate it from other similar behaviors; later, I will provide a conceptual approach to the subjetc, with special consideration of its treatment in Law and comparative doctrine; will review the main foundations in favor and against their criminalization; finally, I aims to determine whether the subsumption of sexting is possible under the offences of infantile-juvenile pornography or those typified in the art. 161-A of our criminal code, as it is the way in which other legislations, such as the Spanish and American, have dealt with the matter.